An integrated approach for the measurement of inequality, poverty and richness - Crespo, Nuno (2013)
We propose a new and integrated approach to the measurement of inequality in income distribution, poverty, and richness. In the context of the poverty and richness measures, we consider the three dimensions usually analysed – incidence, intensity, and severity. The proposed broad set of indicators is easy to calculate and is based on a neutral income inequality concept. The method also allows an objective interpretation of the values for each measure, a decomposition according to households’ characteristics, and an immediate comparison of the results between countries and time periods. We illustrate the application of the measures with data from Portugal.